2018
DOI: 10.1088/1751-8121/aada43
|View full text |Cite|
|
Sign up to set email alerts
|

Wigner–Smith time-delay matrix in chaotic cavities with non-ideal contacts

Abstract: We consider wave propagation in a complex structure coupled to a finite number N of scattering channels, such as chaotic cavities or quantum dots with external leads. Temporal aspects of the scattering process are analysed through the concept of time delays, related to the energy (or frequency) derivative of the scattering matrix S. We develop a random matrix approach to study the statistical properties of the symmetrised Wigner-Smith time-delay matrix Q s = −i S −1/2 ∂ ε S S −1/2 , and obtain the joint distri… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 77 publications
(287 reference statements)
0
25
0
Order By: Relevance
“…where ∆ N (γ) = i<j (γ i − γ j ) denotes the Vandermonde determinant (here, I have slightly simplified the form given in [101]). This form reduces to (85) for κ → 1, as we now check.…”
Section: Proper Time Delaysmentioning
confidence: 99%
See 2 more Smart Citations
“…where ∆ N (γ) = i<j (γ i − γ j ) denotes the Vandermonde determinant (here, I have slightly simplified the form given in [101]). This form reduces to (85) for κ → 1, as we now check.…”
Section: Proper Time Delaysmentioning
confidence: 99%
“…(118) is precisely the BFB result (85) for β = 2, as it should. Although complicate, the form (115) was used in order to derive the distribution of the Wigner time delay [101]. Extracting the marginal distribution of the proper time or correlations seems however difficult.…”
Section: Proper Time Delaysmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that for weakly open systems (see, e.g. [56]) the lifetime statistics is given by a χ 2 distribution…”
Section: Localizationmentioning
confidence: 99%
“…Statistics of Wigner time delays and related quantities in wave-chaotic scattering attracted a considerable interest for about three decades and is still an active research topic, see [53,54,55,56,57,58,59,60,61,62,63,64] and references therein. Interestingly, τ W (λ) naturally appears in characterization of systems with spatially-uniform absorption.…”
Section: Introductionmentioning
confidence: 99%